Penerapan Metode AHP untuk Memprediksi Pegawai Baru Department Store - Julio Warmansyah (Teknois : Jurnal Ilmiah Teknologi Informasi dan Sains, 2021)
Companies engaged in the retail for staple foodstuffs, especially food, which have outlets evenly distributed throughout Indonesia. Requires a decision support system in an effort to improve the quality of the workforce that will be employed in widespread outlets. With so many workers who will be selected at this workforce recruitment, it requires a system that is able to provide support to companies in selecting many workers. By using the Process Hierarchy Analytical method, by analyzing the criteria for workers including Test Value, Education, Interview results, Distance between Rumam and the Store, with job titles and with 10 samples taken from the Cibinong area, Bogor district, this system provides assistance to HR in managing data to be analyzed on quite a lot of alternatives.